2019
DOI: 10.21873/invivo.11481
|View full text |Cite
|
Sign up to set email alerts
|

β-Hydroxy-β-methylbutyrate Suppresses NF-ĸB Activation and IL-6 Production in TE-1 Cancer Cells

Abstract: Background/Aim: Stress reactions, especially those related to surgery, cause poor convalescence of cancer patients. β-Hydroxyβ-methylbutyrate (HMB) is known to regulate excessive inflammation in the body. The objective of this work was to investigate the capacity of HMB to suppress activation of nuclear factor-kappa B (NF-ĸB) and production of interleukin-6 (IL-6) in a human esophageal squamous cell carcinoma cell line . Materials and Methods: Cell proliferation was measured using the water-soluble tetrazolium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…According to Townsend et al [45], in men, dietary supplementation with HMB can decrease the expression of tumour necrosis factor alpha (TNF-α) and TNF-α receptor 1 (TNFR1) on CD14+ monocytes measured by flow cytometry in circulating blood. In a study by Miyake et al [46], HMB did not influence TE-1 cell proliferation, but it inhibited the production of NF-kB and IL-6 on the TE-1 cancer cell line in vitro. Hoffman et al [47] demonstrated that 23 days of HMB supplementation in combat soldiers can attenuate the inflammatory response (TNF-α, interleukins IL-8 and IL-10, granulocyte colony-stimulating factor (GC-SF), interferon (IFN)-γ, and fractalkine) to intense military training, and maintain muscle quality.…”
Section: Discussionmentioning
confidence: 91%
“…According to Townsend et al [45], in men, dietary supplementation with HMB can decrease the expression of tumour necrosis factor alpha (TNF-α) and TNF-α receptor 1 (TNFR1) on CD14+ monocytes measured by flow cytometry in circulating blood. In a study by Miyake et al [46], HMB did not influence TE-1 cell proliferation, but it inhibited the production of NF-kB and IL-6 on the TE-1 cancer cell line in vitro. Hoffman et al [47] demonstrated that 23 days of HMB supplementation in combat soldiers can attenuate the inflammatory response (TNF-α, interleukins IL-8 and IL-10, granulocyte colony-stimulating factor (GC-SF), interferon (IFN)-γ, and fractalkine) to intense military training, and maintain muscle quality.…”
Section: Discussionmentioning
confidence: 91%
“…HMB's biological effects include changes in protein production, inhibition of proteolysis, and anti-inflammatory actions, which help to preserve muscle mass in both young and old subjects [ 40 , 41 ]. Miyake and coworkers were evaluated the anti-inflammatory effects of HMB in TE-1 cancer cells and reported that HMB administration could downregulate IL-6 production by regulation of inhibitor of kappa B alpha (IĸBα) phosphorylation and reduction of nuclear translocation of NF-ĸB/Rela [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Townsend et al [53], a flow cytometry analysis revealed that the circulating levels of TNF-α (tumour necrosis factor) and TNF-α receptor 1 (TNFR1) in CD14 + monocytes decreased in men whose diets were supplemented with HMB. In an in vitro study of the TE-1 cancer cell line, Miyake et al [54] demonstrated that HMB inhibited the activation of NF-ĸB and IL-6 production. In a study by Hoffman et al [55], the inflammatory response (TNF-α, interleukin (IL)-8, IL-10, granulocyte colony-stimulating factor (GC-SF), interferon (IFN)-γ, and fractalkine) to intense military training was attenuated and muscle quality was maintained in combat soldiers whose diets were supplemented with HMB for 23 days.…”
Section: Discussionmentioning
confidence: 99%